The effect of polyphenol-containing solutions on in situ biofilm formation on enamel and dentin. (November 2020) - Xi, Qingping; Hoth-Hannig, Wiebke; Deng, Shuli; Jin, Xiaoting; Fu, Baiping; Hannig, Matthias
Abstract: Objectives: To investigate the effects of Chinese gallnut extracts and pure tannic acid on in situ biofilm formation on enamel and dentin samples over 24 h. Methods: Bovine enamel and dentin samples were buccally fixed on maxillary splints. Six volunteers wore the splints for 24 h, and rinsed their mouths with tap water (control), 1% tannic acid- and 1% Chinese gallnut extracts-containing solution twice a day, 3 min after the splints were placed in the mouth and before night sleep. Live/dead staining was used for fluorescence microscopic (FM) visualization and quantification of bacteria viability of biofilms formed on enamel and dentin samples. Biofilm coverage was evaluated and recorded by FM and scanning electron microscopy (SEM). In addition, biofilms were analyzed by transmission electron microscopy (TEM). The Kruskal-Wallis test was used to analyze biofilm data. Results: Rinsing with tannic acid- and Chinese gallnut extracts-containing solutions significantly reduced in situ biofilm coverage on enamel and dentin samples ( P < 0.05). The bacterial viability of biofilms formed on enamel samples was significantly reduced compared to the control ( P < 0.05). TEM analysis revealed an increase in pellicle's electron density and thickness and only few or no bacteria adherent to the pellicle in the experimental samples. Conclusions: Rinsing with tannic acid- and Chinese gallnut extracts-containing solutions can effectively inhibit in situ biofilm formation, modify the ultrastructure of biofilms on enamel and dentin surfaces and significantly reduce the bacterial viability of biofilm on enamel surfaces. Clinical significance: Tannic acid- and Chinese gallnut extracts-containing solutions might be used for dental biofilm management.